Gender-Based Violence During COVID-19 Pandemic: A Mini-Review - Mittal, Shalini; Singh, Tushar (Frontiers in Global Women's Health, 2020)
Quarantine, though necessary to reduce COVID19 disease spread, has serious psychological and socially disruptive consequences including a surge in the cases of gender-based violence within the home. This paper attempts to understand the quarantine paradox from a gender perspective and reviews the pattern of the rise in gender violence cases, resultant psychosocial issues, and attempts to create awareness by initiating a discourse urging for a change in the response to the victims of gender-based violence. A review of the available literature on the rise of gender-based violence in the times of current and past pandemics was undertaken. In addition, the secondary data available in the newspaper and other mass media sources focusing on the rise of gender-based violence during the imposed lockdown was included in the review so as to describe the nature and prevalence of the issue, its consequences and the measures taken by the governments to tackle the issue. Gender-based violence has increased during the lockdown period for a number of reasons. A surge in gender-based violence was witnessed during other pandemics and epidemics too. The legislatures and services available for such victims fall short of addressing the obstacles in helping them in the times of quarantine. It can be concluded that the imposition of lockdown has several negative outcomes for women. The surge in gender-based violence in the times of lockdown has highlighted the gender inequality specifically in regard to the safety of women. Strong governmental/ NGOs actions are needed to help women feel safe at home.